(untitled) (Research, Society and Development, 2021)
Introduction: Pregnancy is considered a transitional moment in the female world, since it implies physiological, psychological and social changes in the woman’s life. With the arrival of the technocratic model in obstetric care, the emotional, human and cultural aspects present in this cycle are no longer considered, underestimating the peculiar value of birth care. Objectives: To understand the consequences of the emotional demands of pregnancy in the delivery process of the women attended at the Casa de Parto David Capistrano Filho and to understand the context of meeting the emotional demands of the women assisted at the Casa de Parto David Capistrano Filho. Methodology: This is an exploratory-descriptive study with a qualitative documentary approach. The study is set in the David Capistrano Filho Birthing House located in the city of Rio de Janeiro. The data collection technique consists of analyzing 24 medical records of women hospitalized at Casa de Parto David Capistrano Filho in 2019. Results and discussions:The study found that pregnancy covers emotional demands that can be caused or aggravated by external factors such as lack family support, traumas, mourning, as well as the personal history of mental illnesses, which can be identified through the singularity of care and active listening during care. Final considerations: Demands are capable of causing important emotional imbalances if they are not worked on during prenatal care, which can lead to prolonged labor and thereby increase the sensation of pain.